Lei natural e lei civil em Hobbes - Gomes, Rita Helena Sousa Ferreira (Educação e Filosofia, 2008)
A lei natural aparece de forma bastante peculiar na filosofia hobbesiana, assim como é peculiar a relação que a lei natural estabelece com a lei civil. Neste artigo defenderemos a ideia de que na teoria hobbesiana a lei natural é esvaziada de conteúdo, sendo este determinado pela vontade do soberano expressa nas leis civis.Palavras-chave: Hobbes; Lei natural; Lei civil. Abstract: Natural law appears in a singular way in Hobbes’ philosophy as the same way as it happens to the relation which the natural law establishes with the civil law. In this paper we will defend that the notion of natural law, in the Hobbesian philosophy, is empty of content. Thus its content is determined by the will of the sovereign expressed in the civil laws.Keywords: Hobbes; Natural law; Civil law.